ECONOMETRIC MODELING OF EDUCATIONAL SYSTEM DEVELOPMENT USING COMPUTER MATHEMATICS AND ICT - Mukhitdinov, Poshokulova, Khudayar Suyunovych, Mokhigul (THE INNOVATION ECONOMY, 2024)
This article develops conclusions and proposals based on econometric modeling of the development of the educational system using computer mathematics and ICT.